Almost goodbye - Mala Hayati Abdul Khir (2014)
Almost Goodbye is a visual exploration of the photographer’s perspective towards life. The project started out due to an existential crisis faced by the artist as she went through her daily mundane activities. Her sense of detachment from reality and her environment allowed her to explore different means to portray her feelings. Many may refuse to accept the artist’s perspective by saying “maybe all you need is a holiday.” However, what the artist needed is not a holiday but to be able to be physically and emotionally present.